PREVALENCE OF RESISTANCE TO CLINICALLY SIGNIFICANT ANTIBIOTICS AGAINST Escherichia coli ISOLATED FROM HOLY RIVER GANGA, INDIA - Chaudhary, Shiwani; Singh, Dushyant; Dimri, Amita Gaurav; Pillai, Aishwarya; Aggarwal, M.L. (Journal of Biomedical and Pharmaceutical Research, 2018)
Ganga is a divine water body which has acquired a status of mother goddess in Indian culture civilization. Ganga water is considered as sacred water and Hindu rituals from birth to death cannot be consecrated without Ganga water. The microbiological quality of holy river Ganga, life sustaining surface water resource for large population of northern India is adversely affected due to rapid industrialization and population growth. The current investigation surveyed on total number of 10 water samples collected from river Ganga flowing in different cities of India. The samples were analyzed for Most Probable Number (MPN) of coliforms and found to be in the range of 940 organisms to 33000 organisms per 100ml. Similarly, MPN Fecal coliform was done at an incubation of higher temperature, and resulted from lower of 109 organisms to a higher at 2800 organisms per 100ml of samples analyzed. The Ganga water samples also showed the presence of Escherichia coli and further its antibiotic susceptibility pattern was performed by Kirby Bauer Agar well diffusion method. Various clinical significant antibiotics were used namely Streptomycin, Kanamycin, Meropenem, Norfloxacin, Ciprofloxacin, Ampicillin, Sulbactum and Tazobactum. All isolated Escherichia coli strains were found resistant to Tazobactum. The isolated E.coli from upstream water of Varanasi has shown resistance towards four out of eight antibiotics used. Escherichia coli present in all the samples have shown susceptibility towards Meropenem and Ciprofloxacin.Keywords: Ganga water, microbiological quality, Most Probable Number (MPN) of Coliform, MPN Faecal coliform, Escherichia coli, Antibiotic susceptibility and resistance